Cultural And Educational Infrastructure Of The Southern Regions Of Uzbekistan During The Years Of Independence (Eurasian Journal of Humanities and Social Sciences, 2026)
Based on archival sources and statistical data, this article analyzes the formation, development, and systemic problems faced by the cultural and educational infrastructure of the southern regions of Uzbekistan during the years of independence. The study highlights the shrinking trends of club institutions and the library network, the condition of the material and technical base, as well as the problems of personnel potential and their education levels in rural areas. Furthermore, the measures implemented by the state to finance the sector and provide social protection for its employees are outlined.